Integrated approaches for the recognition of small molecule inhibitors for Toll-like receptor 4 - Shailya Verma; Purushotham Reddy; R. Sowdhamini (Computational and Structural Biotechnology Journal, 2023)
Toll-like receptors (TLRs) are pattern recognition receptors present on the surface of cells playing a crucial role in innate immunity. One of the TLRs, TLR4, recognizes LPS (Lipopolysaccharide) as its ligand leading to the release of anti-inflammatory mediators as well as pro-inflammatory cytokines through signal transduction and domain recruitment. TLR4 homodimerizes at its intracellular TIR (Toll/interleukin-1 receptor) domain that helps in the recruitment of the TRAM/TICAM2 (TIR domain-containing adaptor molecule 2) molecule. TRAM also contains TIR domain which in turn, dimerizes and functions as an adapter protein to further recruit TRIF/TICAM1 (TIR domain-containing adaptor molecule 1) protein for mediating downstream signaling. Apart from LPS, TLR4 also recognizes endogenous ligands like fibrinogen, HMGB1, and hyaluronan in autoimmune conditions and sepsis. We employed computational approaches to target TRAM and recognize small molecule inhibitors from small molecules of natural origin, as contained in the Super Natural II database. Finally, cell reporter assays and NMR studies enabled the identification of promising lead compounds. Hence, this study aims to attenuate the signaling of the TLR4-TRAM-TRIF cascade in these auto-inflammatory conditions.